An improvement of a telephone hand-set for high DB response persons / Siti Zauyah Ismail - Ismail, Siti Zauyah (1995)
The purpose of this project is to improve the audibility of speech during telephone conversation for the hard of hearing. In general hearing impaired are a group of people with hearing problems. A telephone model S2000A and a 5 octave equaliser is used in the design. The output of the telephone i.e the receiving call are modified to a certain level which gives better clarity to the hearing impaired person. This telephone can also be utilised by the non-hearing impaired person by switching off the equaliser. Another features of this telephone will be a light indicator to visually help the hearing impaired notice incoming calls. The light will flashes out as the telephone rings. A hearing aid is not required when using this telephone due to sufficient amplification.